Transcription factors NF-YB involved in embryogenesis and hormones responses in Dimocarpus Longan Lour - Tang, Mengjie; Gao, Xiaoli; Meng, Wenyong; Lin, Jindi; Zhao, Guanghui; Lai, Zhongxiong; Lin, Yuling; Chen, Yukun (Frontiers in Plant Science, 2023)
NF-YB transcription factor is an important regulatory factor in plant embryonic development. In this study, 15 longan NF-YB (DlNF-YB) family genes were systematically identified in the whole genome of longan, and a comprehensive bioinformatics analysis of DlNF-YB family was performed. Comparative transcriptome analysis of DlNF-YBs expression in different tissues, early somatic embryogenesis (SE), under different light and temperature treatments, revealing its specific expression profiles and potential biological functions in longan SE. The qRT-PCR results implied that the expression patterns of DlNF-YBs were different during SE and the zygotic embryo development of longan. Supplementary 2,4-D, NPA, and PP333 in longan EC notably inhibited the expression of DlNF-YBs, ABA, IAA, and GA3 suppressed the expressions of DlNF-YB6 and DlNF-YB9, but IAA and GA3 induced the other DlNF-YBs. Subcellular localization indicated that DlNF-YB6 and DlNF-YB9 were located in the nucleus. Furthermore, verification by the modified 5'RLM-RACE method demonstrated that DlNF-YB6 was targeted by dlo-miR2118e, and dlo-miR2118e regulated longan somatic embryogenesis (SE) by targeting DlNF-YB6. Compared with CaMV35S actuated GUS expression, DlNF-YB6 and DlNF-YB9 promoters significantly drove GUS expression. Meanwhile, promoter activities were induced to the highest by GA3 but suppressed by IAA. ABA induced the activities of the promoter of DlNF-YB9, whereas it inhibited the promoter of DlNF-YB6. Hence, DlNF-YB might play a prominent role in longan somatic and zygotic embryo development, and it is involved in complex plant hormones signaling pathways.